Reducing hospital admissions in older care home residents: a 4-year evaluation of the care home innovation Programme (CHIP) - Clarissa Giebel; Debbie Harvey; Asangaedem Akpan; Peter Chamberlain (BMC, 2020)
Abstract Background Older care home residents frequently attend emergency departments with a high conversion to admissions. For this purpose, a novel Care Home Innovation Programme (CHIP) was introduced with the aim of reducing potentially avoidable hospital admissions by 30%. The aim of this study is to evaluate the implementation of this innovative service in practice. Methods A total of 32 care homes with 1314 beds in South Sefton, Merseyside were invited to sign up to CHIP which was launched in April 2015 and continued in its entirety until June 2018. As part of the CHIP, care home matrons were introduced, new protocols were developed to address common presentations, a 24-h 7-day a week televideo system installed across all homes, and a quarterly training collaborative brought care homes together to learn and share good practices together. Data on emergency calls and calls resulting in conveyances were recorded over a four-year period, and analysed using frequency analysis. Results In comparison to the 12 months prior to launch, over a four-year period, implementation of the CHIP resulted in a 15% reduction of emergency calls, and in a 19% reduction of conveyances to hospital. Conclusions The South Sefton CHIP demonstrated itself an effective programme in reducing conveyances and consequently, hospital admissions of care home residents. This model will be superseded by the enhanced health in care homes being promoted by the NHS Long Term Care Plan.